(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
In this paper, we propose a universal registration method for the body scanner consists of multiple fixed sensors. Firstly, a new double-faced checkerboard is designed to apply calibration method into the initial estimations of the relative poses of point clouds. Secondly, ICP (Iterative Closet Point) algorithm is utilized for further registration. Since ICP algorithm may fail in situations of outliers, ambiguity or missing data, we make full use of the geometry feature of creased papers to solve these problems. A new body scanning system with fast capture speed is also proposed to validate our method. The experiment results demonstrate our approach is robust and fast.